Integrative analysis of the ovarian metabolome and transcriptome of the Yaoshan chicken and its improved hybrids - Miao, Xiaomeng; Wu, Tian; Pan, Hongyuan; Zhang, Yalan; Liu, Jia; Fan, Ying; Du, Lin; Gong, Yu; Li, Liang; Huang, Tengda; Ning, Zhonghua (Frontiers in Genetics, 2024)
Laying performance is a key factor affecting production efficiency in poultry, but its molecular mechanism is still indistinct. In this study, Yaoshan chickens, a local breed in Guizhou, China, and merchant chickens (GYR) with higher egg yield after the three-line cross improvement hybridization of Yaoshan chickens were used as animal samples. To explore the regulatory mechanism of the diversities in laying performance, RNA-seq and ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) were used to describe the transcriptional and metabolic profiles of the ovaries of Yaoshan and GYR chickens. At the transcriptional level, 288 differentially expressed genes were upregulated in Yaoshan chickens and 353 differentially expressed genes were upregulated in GYR chickens. In addition, GSEA showed that ECM-receptor interactions and the TGF-β signaling pathway were restrained, resulting in increased egg production in GYR chickens. Furthermore, the upregulation of thiamine and carnitine was identified by metabolomic analysis to facilitate the laying performance of hens. Finally, comprehensive analyses of the transcriptome and metabolome found that thiamine and carnitine were negatively correlated with ECM-receptor interactions and the TGF-β signaling pathway, which jointly regulate the laying performance of Yaoshan chickens and GYR chickens. Taken together, our research delineates differences in the transcriptional and metabolic profiles of the ovaries of Yaoshan and GYR chickens during the peak egg production period and provides new hypotheses and clues for further research on poultry egg production performance and the improvement of economic benefits.